SEG Technical Program Expanded Abstracts 2014 2014
DOI: 10.1190/segam2014-0186.1
|View full text |Cite
|
Sign up to set email alerts
|

Study on the induced polarization model in the exploration for shale gas in southern China

Abstract: Shale gas is becoming increasingly important exploration and production targets. Geological study has showed that the rich shale in southern China has good quality for exploitation. Due to the unique storage condition and continuous complicated accumulation pattern of shale gas, it is difficult to use conventional geophysical method to predict sweet spots. Complex resistivity (CR) method has been used to detect hydrocarbon for more than ten years, because laboratory studies of measureable induced polarization(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 10 publications
0
11
0
Order By: Relevance
“…The Southern China have more sets of shale formation and a large number of studies have been carried out in the area on rock samples from shale gas reservoirs (Yan et al 2014). The shale in the Silurian Longmaxi formation to the Ordovician Wufen formation and the lower Cambrian Qiongzhusi formation have rich organic matter, high maturity and good conditions for storage of shale gas.…”
Section: Site Description and Available Datasetmentioning
confidence: 99%
See 3 more Smart Citations
“…The Southern China have more sets of shale formation and a large number of studies have been carried out in the area on rock samples from shale gas reservoirs (Yan et al 2014). The shale in the Silurian Longmaxi formation to the Ordovician Wufen formation and the lower Cambrian Qiongzhusi formation have rich organic matter, high maturity and good conditions for storage of shale gas.…”
Section: Site Description and Available Datasetmentioning
confidence: 99%
“…Based on Cole-Cole dielectric dispersion model (Cole and Cole 1941), many other empirical models have been employed to fit the complex electrical response of rocks and soils. Yan et al (2014) attest that the relaxation model from Pelton et al (1978) is one of the most used model in which the resistivity of the mineralized porous rock is expressed as:…”
Section: Spectrum Parameters Inversionmentioning
confidence: 99%
See 2 more Smart Citations
“…Xiang et al (2014) confirmed that the dispersion characteristics of a shale complex resistivity are correlated with the TOC content. Yan et al (2014) demonstrated that pyrite is a key to predicting shale TOC content. The complex resistivity charge rate and the resistivity anomaly range can effectively be utilized to match seismic "sweet spots".…”
Section: Introductionmentioning
confidence: 99%